Monolingualism and bilingualism : lessons from Canada and Spain - Wright, Sue, 1947- (Multilingual Matters, 1996)
"There is an urgent need at the heart of linguistic theorising to take account of bi- and multilingual perspectives. In the field of language planning, issues of bilingualism are often perceived through monolingual filters and resolved by monolingual responses. In this volume issues of monolingualism, multilingualism and identity are addressed directly in detailed studies of Canada and Spain." "John Edwards and Charlotte Hoffmann are both well-known authorities on bilingualism and problems associated with language in multilingual societies. In this book they provide state of the art articles on Spain and Canada. Their insights are useful in a period of evolution in both these countries." "After each of the articles, which were presented in a seminar series, there is a transcript of the debate which followed. The invited audiences are all scholars working on the area or in allied fields."--Jacket.